A Succinct Overview of Virtual Reality Technology Use in Alzheimer’s Disease - García-Betances, Rebeca I.; Arredondo Waldmeyer, María Teresa; Fico, Giuseppe; Cabrera-Umpiérrez, María Fernanda (Frontiers in Aging Neuroscience, 2015)
We provide a brief review and appraisal of recent and current virtual reality (VR) technology for Alzheimer’s disease (AD) applications. We categorize them according to their intended purpose (e.g. diagnosis, patient cognitive training, caregivers’ education, etc.), focus feature (e.g. spatial impairment, memory deficit, etc.), methodology employed (e.g. tasks, games, etc), immersion level, and passive or active interaction. Critical assessment indicates that most of them do not yet take full advantage of virtual environments with high levels of immersion and interaction. Many still rely on conventional 2D graphic displays to create non-immersive or semi-immersive VR scenarios. Important improvements are needed to make VR a better and more versatile assessment and training tool for AD. The use of the latest display technologies available, such as emerging head-mounted displays and 3D smart TV technologies, together with realistic multi-sensorial interaction devices, and neuro-physiological feedback capacity, are some of the most beneficial improvements this mini-review suggests. Additionally, it would be desirable that such VR applications for AD be easily and affordably transferable to in-Home and nursing home environments.